Natural Selection : Domains, Levels, and Challenges. - Williams, George C. (Oxford series in ecology and evolution ;, 1992)
In this work, George C. Williams--one of evolutionary biology's most distinguished scholars--examines the mechanisms and meaning of natural selection in evolution. Williams offers his own perspective on modern evolutionary theory, including discussions of the gene as the unit of selection, clade selection and macroevolution, diversity within and among populations, stasis, and other timely and provocative topics. In dealing with the levels-of-selection controversy, he urges a pervasive form of the replicator-vehicle distinction. Natural selection, he argues, takes place in the separate domains.